Peripapillary Choroidal Neovascularization as an Unusual Complication of POEMS Syndrome. Issue 1 (2017) - Nicolai, Heleen; Cassiman, Catherine; Delforge, Michel; Leys, Anita
Purpose: To report the association of polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome with bilateral papilledema and bilateral choroidal neovascularization (CNV) in a 61-year-old man and to compare our findings with data from a review of the literature. Case report: Diagnosis of POEMS syndrome was based on paraproteinemia immunoglobulin A lambda associated with progressive sensorimotor peripheral neuropathy and increased serum vascular endothelial growth factor (VEGF) levels. Shortly later, loss of vision of the left eye (LE) was noted and bilateral papilledema was observed with peripapillary hemorrhages and papillomacular subretinal fluid. Lenalidomide 25 mg daily and weekly dexamethasone 20 mg were administered and the patient was followed up closely. The systemic complaints initially were controlled and peripheral neuropathy improved. Regression of the papilledema and hemorrhages was observed as well as regression of the papillomacular edema in the LE. However, after a few months, the systemic VEGF levels increased, and an active CNV was diagnosed in the LE. Melphalan and prednisone were administered systemically, and the CNV was treated with bevacizumab intravitreal injections and these treatments proved to be effective. Conclusions: Optic disc edema is reported frequently in POEMS syndrome but complication with CNV is rare, this being the second reported case.